연령별 신체활동에 따른 대사성질환과의 관계 - 임효경; Hyo Kyung Lim; 설재웅; Jae Woong Sull; 박범석; Beom Seok Park; 문지영; Ji Young Mun; 홍민화; Min Hwa Hong; 이유리; Yoori Lee; et al. (Korean journal of clinical laboratory science, 2018)
본 연구의 목적은 2014년 조사되어진 제 6기 2차 국민건강영양조사 자료를 바탕으로 연령별 신체활동에 따른 대사성질환과의 관계를 파악하여 연령별 신체활동에 따른 대사성질환과의 관련성을 규명하여 예방적 기초자료를 제공하기 위한 연구이다. 본 연구는 제 6기 2차(2014) 국민건강영양조사의 자료를 이용하여 수행되었다. 정상군의 382명과 대사질환군의 1,525명을 총 9,701명의 설문 응답자 중 관련 자료가 없는 2,506명을 제외하고 총 7,295명을 분석했다. 본 연구에서 신체활동은 국제신체활동 설문지 (IPAQ)를 기반으로 재분류 되었다. 대사증후군의 정의는 2004년 개정 된 NCEP-ATP III에 근거하여 다음과 같은 결론을 얻었다. 연령에 따른 대사성질환과 신체활동과의 관계에서 10∼29세 정상군과 50∼69세의 대사질환군에서 혈색소, 적혈구용적, 크리아티닌의 수치는 고강도 신체활동이 수행되었을 때 증가했고 저강도 신체활동을 수행되었을 때 감소했다. 30∼49세의 정상군과 대사질환군에서 고밀도 지단백 콜레스테롤 수치는 고강도 신체활동이 수행되었을 때 증가했지만, 저강도 신체활동이 수행되었을 때 감소하였다. 따라서 연령과 운동강도가 고밀도 지단백 콜레스테롤 수치에 미치는 영향을 조사하였다. 결과는 정상군에서 연령과 운동강도에 따라 고밀도 지단백 콜레스테롤 수치에 차이는 없었지만 대사질환군에서는 연령에 따라 고밀도 지단백 콜레스테롤 수치가 감소하였고 운동강도에 따라 증가하였다. 종합하면, 본 연구의 결과는 대사질환군에서 고밀도 지단백 콜레스테롤 수치는 고강도 신체활동에서 긍정적인 효과를 나타내고 연령은 부정적인 효과를 나타냈다. 이러한 결과는 우리가 신체활동과 연령에 따라 대사성질환을 더 잘 이해하는데 도움이 될 수 있다. Metabolic disease is associated with abdominal obesity, high blood pressure, and dyslipidemia. Physical activity has beneficial effects on a variety of diseases. This study examined the relationship between metabolic diseases and physical activity according to age. Among a total of 7,295 subjects, the data from 382 individuals in the normal group and 1,525 persons in the metabolic disease group were analyzed. The data were analyzed statistically by one-way ANOVA, the Pearson's correlation coefficient, and multiple regression analysis. The levels of hemoglobin (HB), hematocrit (HCT), and creatinine (CR), were elevated when a high-intensity physical activity was performed, but they were reduced when a low-intensity physical activity was performed in the normal group aged 10∼29 years and the metabolic disease group aged 50∼69 years. In the normal group and metabolic disease group aged 30∼49 years, the level of high density lipoprotein cholesterol (HDL-C) was elevated when high-intensity physical activity was conducted, whereas it was reduced when low-intensity physical activity was performed. No difference in the level of HDL-C depending on age and exercise intensity was observed in the normal group; the level of HDL-C decreased with age and increased with exercise intensity in the metabolic disease group. Physical activity has different effects in metabolic disease depending on age.